2012
DOI: 10.1165/rcmb.2011-0135oc
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniae CARDS Toxin Induces Pulmonary Eosinophilic and Lymphocytic Inflammation

Abstract: Mycoplasma pneumoniae causes acute and chronic lung infections in humans, leading to a variety of pulmonary and extrapulmonary sequelae. Of the airway complications of M. pneumoniae infection, M. pneumoniae-associated exacerbation of asthma and pediatric wheezing are emerging as significant sources of human morbidity. However, M. pneumoniae products capable of promoting allergic inflammation are unknown. Recently, we reported that M. pneumoniae produces an ADP-ribosylating and vacuolating toxin termed the comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
92
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 41 publications
0
92
1
1
Order By: Relevance
“…Due to the absence of a cell wall, mycoplasmas do not possess endotoxin, and M. gallisepticum does not produce any known exotoxin based on sequence homology to known toxin genes (12)(13)(14)(15), including the well-characterized CARDS toxin of Mycoplasma pneumoniae (16). Thus, it remains unknown how M. gallisepticum mediates the severe inflammatory response that ostensibly provides a rich supply of nutrients and an ecological niche well tailored to chronic infection.…”
mentioning
confidence: 99%
“…Due to the absence of a cell wall, mycoplasmas do not possess endotoxin, and M. gallisepticum does not produce any known exotoxin based on sequence homology to known toxin genes (12)(13)(14)(15), including the well-characterized CARDS toxin of Mycoplasma pneumoniae (16). Thus, it remains unknown how M. gallisepticum mediates the severe inflammatory response that ostensibly provides a rich supply of nutrients and an ecological niche well tailored to chronic infection.…”
mentioning
confidence: 99%
“…Several virulence mechanisms of M. pneumoniae are known, including cytoadherence through a polar attachment organelle (14), generation of reactive oxygen species (ROS) (15), and secretion of the community-acquired respiratory distress syndrome (CARDS) toxin (16). Although M. pneumoniae and CARDS toxin induce mucin expression (9,10,17), the signal pathways within the airway epithelium that regulate the response to M. pneumoniae remain unknown. Previously, we have shown that Pseudomonas aeruginosa induces goblet cell hyperplasia and metaplasia (GCHM) and mucus hypersecretion by secreting the redox-active toxin pyocyanin, which induces STAT6 and epidermal growth factor receptor (EGFR) signaling to inactivate FOXA2, a major transcriptional repressor of GCHM and mucin biosynthesis (18,19).…”
mentioning
confidence: 99%
“…There are evidences that suggest the role of Mycoplasma pneumoniae in asthma exacerbation and possibly as a factor in the pathogenesis of asthma [12]- [15].…”
Section: Discussionmentioning
confidence: 99%